พฤติกรรมการใช้ยาปฏิชีวนะอย่างสมเหตุผลในผู้มารับบริการผู้ป่วยนอก - นรินทร สุขเกษม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This Mix Method Research aims to study a reasonable antibiotic use behavior in among outpatients. The population used in this study are 400 outpatients in community hospitals, Chiang Mai Province, receiving antibiotics, and 20 people are used for the qualitative research. The tools used in the study are a questionnaire for the reasonable antibiotic use behavior and a non-structural interview which is an open-ended question which the content validity is verified by 5 experts. The content validity index was 0.82 and the reliability was 0.74. The data were analyzed by using the descriptive statistics such as number, percentage, mean and standard deviation. The study results showed that; The most reasonable antibiotic use behavior is in a good level. The top 3 behaviors includes that 1) Never use or grind antibiotics to apply on the wound directly for healing (80.25%), 2) Never taking expired antibiotics (75.50%), and 3) In the past 1 month, never taking antibiotics more than 2 times (70.25%) respectively. The interview results showed that the most of the samples know antibiotics, but often called "Disinfectant" or "Anti-inflammatory drug", and use to treat sore throat or urinary tract infection. In term of medicine storage, they able to answer all questions completely, and continue to take the medicine every day until the medicine runs out. The suggestions from the research can be used as basic information for analyzing the reasonable antibiotic use behavior in community hospitals and developed to be in accordance with reasonable drug use guidelines further.